BRCA1: An Endocrine and Metabolic Regulator - Werner, Haim (Frontiers in Endocrinology, 2022)
The breast and ovarian cancer susceptibility gene (BRCA1) is a tumor suppressor whose mutation has been associated with the development of breast, ovarian and, probably, other malignancies at young ages. The BRCA1 gene product participates in multiple biological pathways including the DNA damage response, transcriptional control, cell growth and apoptosis. Inactivating germline mutations of the BRCA1 gene can be detected in a substantial portion of families with inherited breast and/or ovarian cancer. While the genomic and cancer-related actions of BRCA1 have been extensively investigated, not much information exists regarding the cellular and circulating factors involved in regulation of BRCA1 expression and action. The present review article dissects the emerging role of BRCA1 as an important regulator of various endocrine and metabolic axes. Experimental and clinical evidence links BRCA1 with a number of peptide and steroid hormones. Furthermore, comprehensive analyses identified complex interactions between the insulin/insulin-like growth factor-1 (IGF1) signaling axis and BRCA1. The correlation between metabolic disorders, including diabetes and the metabolic syndrome, and BRCA1 mutations, are discussed in this article.